Heterotic Patterns Among Ten Pearl Millet Populations - Dutt, Yagya; Baniwal, C R (Annals of Arid Zone, 2016)
Ten pearl millet [Pennisetum glaucum (L.) R.BR. Emend Stuntz] populations were evaluated following diallel mating design (excluding reciprocals) for determining the heterotic patterns among the ten populations and their crosses, and partitioning of heterosis into average heterosis, variety heterosis, specific heterosis, and further to identify base populations for intra- and inter-population improvement programme. In heterotic patterns, average heterosis is more important for characters, namely, grain yield and day to 50% flowering, and specific heterosis has a major role in IDOO-grain weight. In the present investigation, the heterotic patterns indicated that the populations RVPT 93 (102) and crosses HTP88 x HMP9102 x RVPT93 (102), RVPT93(102) x ICMV94774 and HP8601 x ICMV95778 can be successfully exploited as base material for development of inbred lines for hybrids and to develop improved population varieties.